Perspektif ASEAN terhadap Ekonomi Sirkular - Satibi, Iswanda F. (Journal of Economics Development Issues, 2025)
This paper investigates the rapid growth of circular economy (CE) research across ASEAN countries by focusing on publication trends and institutional contributions. In this paper, we used bibliometrics analysis for searching Lens.org from 2016 to 2025 and discovered a total 640 scholarly works published during this period. In particular after 2020, the number of publications increased at a high speed. Indonesia, Malaysia, Vietnam, Thailand, and Singapore occupy the frontrank in research output. This is not only because of their policy support, but also that they have more sophisticated research infrastructure. In addition to the article type, we also obtained figures on changes in publication venues. Journals continue to be the main place for publication, while Open Access articles gain more citations on average. "Circular economy", "business" "biology", "ecology", "economics" emerged as the top five fields of study, which today are apparently synonymous with research on CE. Despite these promising developments, there are limitations in our methodology. Our research relied on a very narrow database for example, and quality assessments were lacking. In future studies, use multiple sources of information such as patent statistics as well as evaluate the research impact. In this way we will be able to gain a more comprehensive understanding of how CE is developing in ASEAN countries.